Secure Data Communication for Wireless Mobile Edge Computing Based on Artificial Noise and Security Code. (October 2020) - Lv, Zhining; Tang, Jie; Deng, Wei; Qiao, Zhongwei; Wen, Hong; Du, Yu
Abstract: As increasing threat to wireless mobile edge computing communication and high cost of conventional encryption implement in wireless mobile edge computing environments. The physical layer security has aroused widespread interests to increase the secure transmission and communications of mobile edge computing data communication in wireless networks. This work investigates the mobile edge computing secure communication by MIMO beamforming and artificial noise (AN) system with secure code. From practical consideration, in this work, we consider a coded system and investigate its achievable secrecy rate under the realistic wiretap code with limited code length and modulation. We proposed the mobile edge computing secure transmission scheme which could make almost zero information obtained by the unknown eavesdroppers with keeping certain quality of BER performance for the main channel simultaneously. The simulation results verify this proposed mobile edge computing secure transmission scheme performance. It shows great implement ability.